PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN: The Effect of Relationship Management and Service Quality on Customer Satisfaction - Dodi Putra Sirait (DIGEST MARKETING, 2018)
The purpose of this study is to determine the partial and simultaneous effect of customer relationship management and service quality on customer satisfaction, especially for the owner of matahari club card (MCC) on beauty service. The data collection is conducted by using questionnaires. Data analysis used multiple linear regression, used SPSS as statistical procedur examinatnion. The results showed that customer relationship management and service quality of partially and simultaneously have positive and significant effects on customer satisfaction in PT. Matahari Department Store Jambi City. Keywords: Customer Relationship Management, Service Quality, and Customer Satisfaction